2000
DOI: 10.4049/jimmunol.165.8.4522
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E1A Oncogene Expression in Tumor Cells Enhances Killing by TNF-Related Apoptosis-Inducing Ligand (TRAIL)

Abstract: Expression of the adenovirus serotype 5 (Ad5) E1A oncogene sensitizes cells to apoptosis by TNF-α and Fas-ligand. Because TNF-related apoptosis-inducing ligand (TRAIL) kills cells in a similar manner as TNF-α and Fas ligand, we asked whether E1A expression might sensitize cells to lysis by TRAIL. To test this hypothesis, we examined TRAIL-induced killing of human melanoma (A2058) or fibrosarcoma (H4) cells that expressed E1A following either infection with Ad5 or stable transfection with Ad5-E1A. E1A-transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 64 publications
4
41
0
Order By: Relevance
“…The Hs766T cells were highly insensitive to virusinduced cell killing with EC 50 values of 24 400 ± 8000, 17 400±5800 and 15 000±3000 ppc for Ad5, dl922-947 and dl1520, respectively. There were no significant differences between viruses in the murine Panc02 cells (EC 50 values of 2000 ppc) (Figure 1a). The non-replicating E1A-deleted mutant dl312 did not induce cell death at concentrations up to 1 Â 10 5 ppc in any cell line.…”
Section: Resultsmentioning
confidence: 99%
“…The Hs766T cells were highly insensitive to virusinduced cell killing with EC 50 values of 24 400 ± 8000, 17 400±5800 and 15 000±3000 ppc for Ad5, dl922-947 and dl1520, respectively. There were no significant differences between viruses in the murine Panc02 cells (EC 50 values of 2000 ppc) (Figure 1a). The non-replicating E1A-deleted mutant dl312 did not induce cell death at concentrations up to 1 Â 10 5 ppc in any cell line.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the previous report by Yamanaka et al, 34 who showed that six HCC cell lines were resistant to TRAIL, we found that the Hep3B cells were sensitive to TRAIL by the Caspase-3 assay ( Figure 6). The different results may be due to the conformational structure of recombinant TRAIL, 35 E1A expression 36 or E1B-19k gene deletion. 37 Expression of AFP in human HCC cells varies greatly, ranging from essentially undetectable to extremely high levels.…”
Section: Discussionmentioning
confidence: 99%
“…Because constitutive endocytosis and predominant intracellular location of some of the TRAIL receptors were reported previously (44,45), further studies are needed to determine whether TRAIL produced by SG235-TRAIL ligates the death receptors within intracellular organelles and thus triggers apoptosis. Additionally, adenovirus E1A gene expression in tumor cells was reported to enhance killing by TRAIL (46), which may contribute to enhanced apoptosis induced by SG235-TRAIL.…”
Section: Discussionmentioning
confidence: 99%